2019
DOI: 10.1101/19014118
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Out of hospital cardiac arrests in the Gulf Region: a scoping review

Abstract: Background Out-of-hospital cardiac arrest (OHCA) is a major cause of mortality worldwide. Recent studies demonstrated low survival rates in Middle Eastern countries. Anecdotally there are unique demographic, cultural and logistical challenges in this region. However, there remains a paucity of data published on OHCA in the Middle East. In order to address OHCA in a meaningful manner in the region, we first need to quantify the issue. Methods We conducted a scoping review of published and grey literature on OH… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…A recent scoping review of the OHCA in the gulf region showed a variety of demographic data, low CPR rates, and fewer ROSCs in the gulf region compared with several western-based studies. 17 In our study, we included a total of 1307 OHCA between April and June 2021. Not a surprise, as 65% of our sample were males, and that was similar to both local and international figures.…”
Section: Discussionmentioning
confidence: 99%
“…A recent scoping review of the OHCA in the gulf region showed a variety of demographic data, low CPR rates, and fewer ROSCs in the gulf region compared with several western-based studies. 17 In our study, we included a total of 1307 OHCA between April and June 2021. Not a surprise, as 65% of our sample were males, and that was similar to both local and international figures.…”
Section: Discussionmentioning
confidence: 99%
“…Our review highlights the safety of clinical roles within the MCC to perform roles that may provide alternatives to traditional transport. However, it is critical to consider that many of our included studies come from highly progressive systems where entry to practice may include baccalaureate training for both paramedics and nurses [55][56][57].…”
Section: Discussionmentioning
confidence: 99%